Spatio-temporal analysis of aerosol concentration over Saudi Arabia using satellite remote sensing techniques - Ali, Md. Arfan; Assiri, Mazen Ebraheem (Penerbit UKM, 2016)
Aerosols are a principal factor in altering climatic dynamics both at regional and global scales. Saudi Arabia is highly affected by aerosols particulates mainly due to the frequent sand and dust storm events in the region. In this context, this study examined Moderate Resolution Imaging Spectroradiometer (MODIS) Deep Blue (DB) Aerosol Optical Depth (AOD) variability both from Terra and Aqua satellites and its relationship with temperature for the period 2002-2007.A comparison between Terra and Aqua DB AOD products were also made in this study. The annual mean AOD analysis based on Terra and Aqua showed a decreasing and increasing trend respectively. Results of the study also showed that the temperature had a strong correlation with Terra DB AOD (r =0.79) than Aqua DB AOD (r =0.68). Overall, DB algorithm was found to be well enough for the assessment of aerosol variability to be conducted over Saudi Arabia.